Green Jobs in the Development of Labor Law in Indonesia - Wandi; Ahmad Rifa’i (Journal of Social Transformation and Regional Development, 2021)
All government and development policies and actions must ask permission for human rights to a good and healthy environment. There should be no more policies contained in laws or regulations under those laws that debate pro-environment constitutional provisions (green laws) or with the reinforcement of other policies that are nuanced environment or green must be in accordance with the laws and regulations. the invitation (green legislation) addresses the mandate in Article 44 of Law Number 32 Year 2009 concerning PPLH. Green work is made a bridge to make future labor laws that are truly approved, so changes to the laws and regulations in the field of employment need to be done. Therefore, decent and environmentally friendly work is linked to the Millennium Development Goals 1 (poverty commitment) and the Millennium Development Goals 7 (environmental protection) which are complementary and not in conflict with each other. Development of  Manpower Law conceptualized Green Jobs, to be effective in the midst of society, the change in law must consider three provisions namely; 1). The change in law was not carried out partially, the change must be resolved, more to the doctrine, norms that are not in accordance with the times. 2. The change must also be included in the way it is applied. 3). It must also be adhered to the rules (rules) that are in accordance with the philosophy of life of the Indonesian people in the hope that the agreed rules can be obeyed by the community, then in those rules (rules) there must be approval and endurance for that made by the government requested.